Statistical Model of Digital Coherent Combining Efficiency in Multi-aperture Receivers - Jing-song XIANG; Xin-hao Lü (Guangtongxin yanjiu, 2022)
In order to mitigate the performance fading of Free-Space Optical (FSO) communication system caused by atmospheric turbulence, a multi-aperture receiving scheme based on digital coherent beam combining is used. Digital coherent beam combining relies on the digital phase alignment algorithm to align the different versions of signals in phase. In this paper, the statistical model of combining efficiency for digital phase alignment is derived in multi-aperture FSO receivers by considering the phase alignment errors at each receiving aperture. It can be expressed as a linear function of chi-square distribution by Satterthwaite approximation. Based on this statistical model, we derive the exact expressions of the mean, variance, and probability density function of the combining efficiency. The simulation results show that this model is valuable under the condition of the different number of aperture and signal-to-noise ratio combinations. Combining efficiency is also compared for Equal Gain Combining (EGC) diversity FSO systems with or without considering aperture selection.